Evaluating the resistance mechanism of Atriplex leucoclada (Orache) to salt and water stress; A potential crop for biosaline agriculture - Alam, Hasnain; Zamin, Muhammad; Adnan, Muhammad; Ahmad, Nisar; Nawaz, Taufiq; Saud, Shah; Basir, Abdul; Liu, Ke; Harrison, Matthew Tom; Hassan, Shah; Alharby, Hesham F.; Alzahrani, Yahya M.; et al. (Frontiers in Plant Science, 2022)
Atriplex leucoclada is a halophytic and native plant having potential use shrub for fodder and landscaping in marginal lands. The response of A. leucoclada to different levels of salt and drought stress was studied using factorial design with four levels of salinity and four drought intensities under the arid climatic conditions. A. leucoclada showed morphological and physiological adaptation to salt and water stress and had no significant effect on survival percentage and growth parameters. On the other hand, increasing water stress had shown major decrease in growth. Water stress treatment decreased the RL of A. leucoclada under low salt stress. However, as supposed, water stress increased the RL under higher salt stress. Plant total nitrogen, phosphorus and potassium content were decreased with increasing water stress only at low salt stress level. As the salt stress increased negative effect of water stress became minimal. Both salt and water stress had increased Na+ and Cl- uptake. Catalase (CAT) activity of A. leucoclada had non-significant effect of salt and water stress levels. Cl- uptake in A. leucoclada increased with increasing water stress at lowest salinity level S1 only. Both salt and water stress had an additive role in increasing ABA and proline content. Higher salt stress levels of S2, S3 and S4 increased proline content with increasing water stress level. CAT activity in leaves of A. leucoclada increased with increasing water stress level under S1 and decreased with increasing water stress under S2, S3 and S4. With increasing water stress level, POD activity of A. leucoclada in leaves also increased. Increasing salinity stress level from S1 to S3 also increased peroxidase. However, at higher salinity stress level of S4 POD activity decreased. APX activity in A. leucoclada increased with increasing salt stress. Similarly increasing water stress also increased the APX activity in A. leucoclada. In conclusion A. leucoclada used salt resistance mechanism to accumulate higher concentrations of salts in its cells. Studied species used physiological adaptation to cope with higher salt stress and ROS (reactive oxygen species) produced.